Compliance of postoperative instructions following the surgical extraction of impacted lower third molars - Ramakrishna S Shenoi; Jignesh G Rajguru; Sargam R Parate; Pranav D Ingole; Sandeep R Khandaitkar; Jui S Karmarkar (Wolters Kluwer Medknow Publications, 2021)
Introduction: The way postoperative care instructions are presented by the professional (verbal and/or written) is the key element that influences quality of treatment. Hence, the aim of the present study was planned to assess the patient's compliance with postoperative care instructions given in different forms following the surgical removal of impacted lower third molars. Materials and Methods: Forty patients scheduled to undergo surgical extraction of impacted lower third molars under local anesthetic were randomly assigned to one of two groups. Before surgery, basic demographic data about age, gender, deleterious habits were recorded. Group A (verbal postoperative care instructions) and Group B (verbal + pictorial postoperative care instructions) were given with a prescription of medication after the surgical removal of impacted lower third molars. Patient were recalled on 7th postoperative day for suture removal and asked to fill the closed-ended questionnaire. Results: Out of 20 patients in each group, one patient from Group A was eliminated as the patient did not turn for the follow-up visit. Therefore, result was based on 39 patients (19 males and 20 females) of age 28-41 years with a mean of 33.2 years (SD ± 3.3). The significance level was set at P < 0.05. The compliance of patients regarding gargling with lukewarm water and mouth opening exercises was seen more significantly in Group B (Pictorial + Verbal). Conclusion: Verbal instructions are inadequate due to difficulty in retention. Hence, a pictorial form of delivering postoperative instructions increases information retention which significantly increases pain relief without extending the analgesic consumption.